(untitled) (SAARC Journal of Agriculture, 2026)
This study aims to investigate the effects of various organic soil amendments on the growth, germination, and survival of summer onion seedlings, conducted during the 2019-2020 cropping seasons at the Spices Research Centre (SRC), Shibganj, Bogura, Bangladesh. The research was performed on sandy loam soil under the subtropical climatic conditions prevalent in the region. Having experiment tested five different soil treatments. Results indicated that the organic amendments significantly influenced seedling growth, with the treatment incorporating a combination of sandy loam, FYM, and cocopeat yielding the best overall performance. The highest germination rate of 91.03% was observed in this treatment, while it also exhibited the tallest seedlings (17.20 cm), the highest number of leaves (5.30 cm), longest roots (6.17 cm) and the greatest root number (7.57). Furthermore, this treatment recorded the highest seedling vigor index (1453.00) and survival rate (88.67%), signifying its effectiveness in promoting robust seedling development. These enhancements positively influenced seedling emergence and establishment, leading to improved seedling vigor and survival. Consequently, the study concluded that organic soil amendments, specifically the combination of FYM with cocopeat and vermicompost, are highly beneficial in improving onion seedling growth and health. This approach can be recommended for the cultivation of summer onions, as it not only supports vigorous seedling establishment but also contributes to sustainable agricultural practices through the use of natural soil enhancements. SAARC J. Agric., 23(2): 63-74 (2025)